The Spread Of Salafi Wahabi Influence: A Study In Terengganu, Malaysia - Nor Hafizi, Yusof; Abdillah Hisham, Ab. Wahab; Ahmad Fauzi, Hassan; Mohd A' Tarahim, Mohd Razali; Fatimah Zaharah, Ismail; Tasnim, Abdul Rahman (2015)
The debate on Salafism and Wahabism is not a recent issue in Muslim’s community. In Malaysia, it has been discussed since the early of the 20th century, during the Islah movement in Egypt and its neighbouring countries. The movement had affected the local Muslim scholars who studied abroad, especially in Saudi Arabia and Egypt, and hence brought back the influence to their homeland. Despite the strong opposition, it continues to expand and the rift between both opposing groups has coloured the scenario of Islamic preaching until now. The objective of this study is to describe the background of the Salafi and Wahabi that it was spread to Malaysia, especially Terengganu. It is also aimed to get to know the associated Muslim scholars in Terengganu and their views on this issue. This is a descriptive study which combines both literature and field study. For the literature part, references such as books, thesis, journal articles, and paper works had been used. Interview sessions with the selected scholars were conducted using structured questionnaires. Based on the findings, it was found out that this movement has been notable in Malaysia as the output from the Islah movement in the Middle East countries. It was also resulted from the spread of this influence by Malaysian students who studied in Mecca, Egypt and India who brought back the influence to Malaysia.